FRI0059 SARCOPENIA IN PATIENTS WITH RHEUMATOID ARTHRITIS. (2nd June 2020) - Tekgoz, E.; Colak, S.; Ozalp, F.; Sonaeren, İ.; Yilmaz, S.; Çinar, M.
Abstract : Background: Sarcopenia is defined as the decrease in strength, mass and function of muscles and may be related with aging, chronic inflammation or malnutrition. Proinflammatory cytokines may be associated with development of sarcopenia. Objectives: The aim of this study was to evaluate sarcopenia in patients with Rheumatoid Arthritis (RA). Methods: One hundred patients with RA (30 Male/70 Female) and 100 healthy controls (30 Male/70 Female) were included in this cross sectional study. According to The European Working Group on Sarcopenia in Older People (EWGSOP2) 2018, three parameters; muscle strength, muscle mass and physical performance, which are evaluated by hand grip strength, Body Impedance Analyzer (BIA) and 6 meters gait speed test, respectively, are used to diagnose sarcopenia. Patients with arthritis in dominant hand joints and ankle joints were excluded. Sarcopenia is defined as the decrease of strength and mass of muscles. On the other hand patients with low muscle strength but normal muscle mass are defined as probable sarcopenia. Results: The mean age was 58.52±10.95 for patients and 56.62±10.08 for controls (p=0.203). Frequency of probable sarcopenia was 35 (35.0%) in RA and 9 (9.0%) in control group (p<0.001). Results of hand grip and 6 meters gait speed tests were lower in RA patients (p=0.002 and p<0.001 respectively). Frequency of probable sarcopenia was higher in females, older patients and patients with longer disease duration. Disease activity and Health Assessment Questionnaire scores were higher in patients with probable sarcopenia compared with patients with no sarcopenia (p<0.05) (Table 1 ). In multivariate regression analysis; age, gender and DAS28 ESR/CRP were associated with hand grip strength (p<0.001, R 2 =0.62) (Table 2 ). Conclusion: Loss of muscle strength in patients with RA may be seen frequently. Longer disease duration and higher disease activity should lead to development of sarcopenia due to chronic inflammation. Sarcopenia potentially effects patients' social lives and daily functions and conceive decrease quality of life. Physicians should be aware of development of sarcopenia during the course of the disease, and take into account the preservative and preventive methods against to sarcopenia including exercise and control of disease activity. Acknowledgments: None to declare Disclosure of Interests: None declared